Task Scheduling Strategies for Utility Maximization in a Renewable-Powered IoT Node; IEEE Transactions on Green Communications and Networking; Vol. 4, iss. 2 - Leithon J. Johann; Suarez L. A. Luis; Anis M. M. Muhammad Moiz; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara (2020, 2020)
Title screen